2018
DOI: 10.17116/jnevro20181183248-56
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in ischemic stroke

Abstract: Today, stroke is the third most common pathology after cardiovascular disease and cancer, as well as the leading cause of disability in the world. Although some progress has been made in the field of primary and secondary stroke prevention over the past few decades, a deeper knowledge of the pathophysiology of the disease is needed to significantly improve diagnosis and therapy. MicroRNA (miRNA) is an important, recently identified class of posttranscriptional regulators of gene expression. MiRNA can be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 88 publications
0
4
0
2
Order By: Relevance
“…MiRNAs dysregulation causes various diseases [ 38 , 39 ]. An increasing number of studies have reported that miRNAs are involved in human cancer [ 40 ], ischemic stroke [ 41 ] and neurodegenerative disorders [ 42 ]. However, the significance of miRNA regulation in the treatment of morphine tolerance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs dysregulation causes various diseases [ 38 , 39 ]. An increasing number of studies have reported that miRNAs are involved in human cancer [ 40 ], ischemic stroke [ 41 ] and neurodegenerative disorders [ 42 ]. However, the significance of miRNA regulation in the treatment of morphine tolerance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that miR-140-5p could inhibit neuronal injury, improve neuron function, and suppress the development of ischemic injury. The effects of miRNAs on the regulation of experimental stroke and in the development of carotid artery stroke, as well as functioning as promising biomarkers of stroke have been reported [35]. Besides, miRNAs have emerged as potential diagnostic and prognostic biomarkers in ischemic stroke has also been discussed [36].…”
Section: Discussionmentioning
confidence: 99%
“…и для богатых холестерином липопротеинов. ЛНП, липопротеины очень низкой плотности и липопротеины промежуточной плотности проникают в субэндотелиальное пространство посредством трансцитоза, где они накапливаются и подвергаются окислению [1,17]. В свою очередь, гипергликемия способствует увеличению циркулирующих нейтрофилов и моноцитов посредством влияния на миелопоэз [1].…”
Section: патофизиологические механизмы развития ссз у пациентов с пре...unclassified